Presence of Arsenic in Argentinian Rices. Strategies to Minimize Them (Global Journal of Science Frontier Research, 2023)
Arsenic As is a ubiquitous chemical element present in nature that is harmful to live beings it has been classified as a carcinogen class 1 and its toxicity depends on its chemical form resulting in the inorganic forms being more toxic than organic forms It is known that rice is one of major contributors to the consumption of inorganic As for humans Because of this the Codex Alimentarius defined as maximum values of total As and inorganic As in polished rice of 0 30 mg kg-1 and 0 20 mg kg-1 respectively Rice is efficient in absorb high amounts of As because anaerobic condition generated from flood increase As availability and mobility Natural resources used for rice production soil and water in Entre R os province of Argentina are characterized by low total contents of As while in white polished rice grains mean value is 0 34 mg total As kg-1 The addition of phosphate fertilizer in many cases depresses rice yields despite the low availability of soil P which would be explained by the release of natural As to soil solution Thus field studies were conducted to evaluate the effect of fertilization and management on the yield of rice and grain As accumulation The effect of irrigation was evaluated oxygenating the soil during the vegetative period which allowed reduces the level of total As in grains without any loss of yield A second study considered the effect of phosphate and zinc fertilization As was also added to test a greater availability of this element in soil The concentration of P and Zn in grain was not affected by the treatments Under natural conditions of low availability of As P and Zn fertilization did not improve yield or affect the absorption of As for rice crop While with the high availability of As the yield was severely affected but the combined addition of P and Zn allowed to mitigate its toxic effect These results are crucial to understanding the dynamics of As in the soil-plant system under field conditions and to developing practical management recommendations